2020
DOI: 10.1038/s41418-020-00668-w
|View full text |Cite
|
Sign up to set email alerts
|

RIP1 kinase activity promotes steatohepatitis through mediating cell death and inflammation in macrophages

Abstract: Hepatocyte cell death and liver inflammation have been well recognized as central characteristics of nonalcoholic steatohepatitis (NASH), however, the underlying molecular basis remains elusive. The kinase receptor-interacting protein 1 (RIP1) is a key regulator of apoptosis, necroptosis and inflammation, we thus hypothesized that the kinase activity of RIP1 may be involved in the pathogenesis of NASH. Wild-type and RIP1 kinase-dead (Rip1 K45A/K45A ) mice were fed with methionine-and choline-deficient diet (MC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 60 publications
2
60
0
1
Order By: Relevance
“…Our findings indicate that upregulation of RIP1 is essentially involved in OA pathogenesis. Receptor-interacting protein kinase 1 has emerged as a crucial regulator in various human diseases such like cancers, neurodegeneration, autoimmune, and inflammatory diseases (Ofengeim and Yuan, 2013;Liu et al, 2015;Ofengeim et al, 2017;Wang et al, 2018;Tao et al, 2020). While the kinase activity of RIP1 mediates the activation of RIP3 and caspase-8 to promote necroptosis and apoptosis respectively, RIP1 also serves as a signaling scaffold to prevent the activation of RIP3 and caspase-8 in a kinase-independent manner, implying the tissue-specific complicated role of RIP1 (Degterev et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that upregulation of RIP1 is essentially involved in OA pathogenesis. Receptor-interacting protein kinase 1 has emerged as a crucial regulator in various human diseases such like cancers, neurodegeneration, autoimmune, and inflammatory diseases (Ofengeim and Yuan, 2013;Liu et al, 2015;Ofengeim et al, 2017;Wang et al, 2018;Tao et al, 2020). While the kinase activity of RIP1 mediates the activation of RIP3 and caspase-8 to promote necroptosis and apoptosis respectively, RIP1 also serves as a signaling scaffold to prevent the activation of RIP3 and caspase-8 in a kinase-independent manner, implying the tissue-specific complicated role of RIP1 (Degterev et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, further investigation indicated that the level of IL‐1β in mouse liver was closely consistent with the level of p‐MLKL in response to APAP exposure, as evidenced by co‐localization of p‐MLKL and IL‐1β 74 . Tao's study demonstrated that RIPK1 activity was promoted in hepatic macrophages after HFD feeding, but hepatic inflammation was obviously alleviated in RIPK1 kinase‐dead (RIPK1 K45A/K45A ) mice compared with WT mice, implying that RIPK1 is required for controlling hepatic macrophage infiltration and activation 75 . Also, the results obtained in both bone marrow–derived macrophages (BMDMs) and primary Kupffer cells (KCs) further confirmed the hypothesis that RIPK1 plays a crucial role in mediating inflammasome activity.…”
Section: Crosstalk Between Necroptosis and Other Ald‐associated Patho...mentioning
confidence: 55%
“…′ kinase activity in hematopoietic-derived macrophages contributed mostly to the disease progression in NASH (31).…”
Section: Programmed Cell Death In Non-alcoholic Steatohepatitis and Fibrosismentioning
confidence: 99%
“…These protective effects were independent of a kinase activity, as RIPK1 K45A kinase dead knock in mice did not improve insulin resistance or reduce obesity on HFD feeding ( 30 ). However, Tao et al observed less liver injury, less steatosis and decreased inflammation in HFD- and MCD-fed RIPK1 K45A mice ( 31 ). Further investigations revealed that RIPK1′ kinase activity in hematopoietic-derived macrophages contributed mostly to the disease progression in NASH ( 31 ).…”
Section: Initiation Of Liver Fibrosismentioning
confidence: 99%
See 1 more Smart Citation